2018
DOI: 10.1016/j.devcel.2018.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Progressive Recruitment of Mesenchymal Progenitors Reveals a Time-Dependent Process of Cell Fate Acquisition in Mouse and Human Nephrogenesis

Abstract: Mammalian nephrons arise from a limited nephron progenitor pool through a reiterative inductive process extending over days (mouse) or weeks (human) of kidney development. Here, we present evidence that human nephron patterning reflects a time-dependent process of recruitment of mesenchymal progenitors into an epithelial nephron precursor. Progressive recruitment predicted from high-resolution image analysis and three-dimensional reconstruction of human nephrogenesis was confirmed through direct visualization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
208
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 180 publications
(233 citation statements)
references
References 43 publications
25
208
0
Order By: Relevance
“…Dissociation of the adult mouse kidney into a representative set of single cells presented a significant challenge beyond protocols extracting cortical nephron progenitor cells from the surface of fetal and newborn mouse kidney (Lindström et al, 2018a). To avoid stress artefacts, we followed a 'cold dissociation' strategy, built around Bacillus licheniformis cold active protease (CAP), which had been successfully used to dissociate newborn (p1) mouse kidneys (Adam et al, 2017), monitoring cell yields by fluorescence-activated cell sorting (see below) and a quantitative PCR assessment of cDNA for cell-type specific markers comparing to undissociated tissue.…”
Section: Adult Mouse Kidney Cell Dissociationmentioning
confidence: 99%
“…Dissociation of the adult mouse kidney into a representative set of single cells presented a significant challenge beyond protocols extracting cortical nephron progenitor cells from the surface of fetal and newborn mouse kidney (Lindström et al, 2018a). To avoid stress artefacts, we followed a 'cold dissociation' strategy, built around Bacillus licheniformis cold active protease (CAP), which had been successfully used to dissociate newborn (p1) mouse kidneys (Adam et al, 2017), monitoring cell yields by fluorescence-activated cell sorting (see below) and a quantitative PCR assessment of cDNA for cell-type specific markers comparing to undissociated tissue.…”
Section: Adult Mouse Kidney Cell Dissociationmentioning
confidence: 99%
“…We related the cell clusters from D29 human kidney organoids (ThF line) to human tissue by comparing them to fetal kidney from the first (8 weeks) and second (17 weeks) trimesters (Lindström et al, 2018b;, and to adult kidney (Fig. 1C, right).…”
Section: Mature Organoids Most Closely Resemble Fetal Kidneymentioning
confidence: 99%
“…These studies confirmed increased expression of Cyp26b1 in ECs compared to non-ECs (Supplemental Fig. 1) (Du et al, 2015;Du et al, 2017;Guo et al, 2019;Hochane et al, 2019;Lindstrom et al, 2018;Sabbagh et al, 2018;Tabula Muris et al, 2018).…”
Section: Cyp26b1 Is Highly Enriched In Lung and Kidney Ecsmentioning
confidence: 53%